Evidence-based digital health interventions for breast cancer survivors' care: an umbrella review - Alba Jiménez-Díaz; Tamara Escrivá-Martínez; Rocío Herrero; Rosa Baños (Internet Interventions)
Introduction: As breast cancer survival rates continue to rise, the number of breast cancer survivors (BCS) requiring supportive care is increasing, placing additional strain on healthcare systems facing resource shortages. In response, digital health is rapidly evolving, and research on eHealth interventions is expanding significantly. Therefore, we conducted an umbrella review to summarize the evidence on digital health interventions aimed at improving health-related outcomes for BCS. Methods: The protocol was preregistered in PROSPERO (CDR42022341837). The Preferred Reporting Items for Overviews of Reviews (PRIOR) were followed. Five databases were searched (Scopus, Web of Science, PubMed, Cochrane Reviews, IEEE Xplore) in July 2022 and updated in April 2024. Systematic reviews and/or meta-analyses examining digital health interventions targeting BCS health-related outcomes were included. Two reviewers independently selected reviews, extracted data, and assessed the quality of the included reviews through AMSTAR-2. Results: Seventeen systematic reviews met the inclusion criteria, and ninety-two original studies on digital health interventions for BCS were identified across them. Overall, digital health interventions seem to improve physical activity outcomes, although effects on quality of life and psychological outcomes are less clear. The quality of most systematic reviews was low, and conclusion should be interpreted with caution. Conclusions: Digital health interventions show some potential in improving health-related outcomes for BCS. However, more robust, theory-driven, and outcome-specific studies are needed to clarify the potential effects of these interventions on the unique needs of specific cancer populations.